ANALISIS TERMAL SOKET LAMPU MOBIL KOMPOSIT EPOXY SERAT NANAS DENGAN PENDEKATAN METODE FEA - Fachriza, Andry; Prabowo, Bambang; Dicky; Zohari, Ahmad; Saputra, Eka Bima (MACHINERY Jurnal Teknologi Terapan, 2024)
The function of the car light socket is to connect electricity to the car lights. The car lights would result in high temperatures and melt if it is used continuously. The electrical short circuits and light sockets made from plastic can also cause melting. This research aims to find a new material for lamp sockets that has high-insulating characteristics. The researcher uses composite materials of epoxy resin and pineapple leaf fiber to make car light sockets. The thermal simulation uses Solidworks software and its parameters obtained from research journals. The maximum and minimum temperatures that resulted from the thermal simulation are 110.916 â„ƒ and 74.849 â„ƒ. The melting temperature of the car light socket in the thermal simulation (pineapple fiber-epoxy resin) is higher than the previous light socket material (plastic) and the temperature when a short circuit occurs. Therefore, the pineapple leaf fiber-epoxy resin composite can be used as for car light sockets.